Promoting African enterprise - Dinwiddy, Bruce (London : Croom Helm in association with the Overseas Development Institute, 1974)
The book sought to establish the extent to which Africans have entered the private sector of commerce and industry as entrepreneurs. It also investigated means of promoting this process. It examined Ghana, Kenya, Malawi, and Swaziland with particular reference to economic and political background; present state of African entrepreneurship; government programme of assistance; commercial banks and expatriate companies.
Includes index.
Includes bibliographical references
lje 17/01/2018
Loans
Keywords: Business enterprises; Africa